Juvenile Angiofibroma - Dubey, Siba P.; Schick, Bernhard; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides a comprehensive up-to-date review of juvenile angiofibroma, with contributions from all relevant specialties. Starting with a brief introduction to the history, etiology and relevant anatomy, the book goes on to discuss the pathology, clinical features and treatment of this disease in depth, concluding with a summary of current controversies. Juvenile Angiofibroma is aimed at a global audience of otolaryngologists, endoscopists, head and neck surgeons, maxillofacial surgeons, pathologists, radiologists and geneticists.
Part I History, Anatomy and Tumor Biology -- Historical Background -- Surgical Anatomy of the Skull Base -- Pathologic and Electron Microscopic Features -- Recent Concept of Etiology -- Part II Clinical and Radiological Diagnosis -- Clinical Presentation -- Juvenile Angiofibroma and the Eye -- Radiological Diagnosis -- Staging Systems and their Use -- Part III Management -- Pre- and Intraoperative Embolization -- Anesthesia and Management of Intraoperative Bleeding -- Endoscopic Surgery -- Endoscopic Excision of Advanced with Skull Base Involvement -- Excision by Midfacial Degloving Approach -- Excision by Modified Transpalatal and Maxillary Swing Approach Excision by Le Fort I Osteotomy Approach -- Excision by Lateral Skull Base Approach -- Combined Neurosurgical and Craniofacial Approach for Large Intracranial Tumor -- Radiation Therapy -- Adjuvant Chemotherapy and Hormonal Therapy -- Part IV Other Issues -- Recurrence of Tumor - Its Prevention and Management -- Extranasopharyngeal Angiofibroma -- Remaining Controversies in Nasopharyngeal Angiofibroma. .
Keywords: Medicine; Otolaryngologic surgery; Pathology; Medicine & Public Health; Head and Neck Surgery; Pathology